ONLINE LEARNING FOR STUDENTS 2014 OF STKIP AL HIKMAH SURABAYA: SCHOOLOGY.COM - Pandu Prasodjo (DIDAKTIKA, 2016)
Educators realize that our education today will have a huge gap with 10 to 20 years latereducation in terms of aims, methods, content, and students' orientation. This is an effect ofthe technology fast development that cannot be separated apart with people prior needs list.That is one reason educators must upgrade their ability especially in information andtechnology knowledge in order to make them able to use the development of technologywhich can be applied in learning processes.Online learning is an option to conduct teaching and learning activity for a lot of peoplewho come from many places around the world at the same time in one class. Onlinelearning is different from distant learning and e-learning even though they havesimilarities. Through online learning all students are enthusiast conducting teaching andlearning activities, it could accommodate a lot of people in the same time to conductteaching and learning activity, it is valuable for adult learners, facilitators role is importantto maintain students' willingness to study, and it is limited by distance and time in certaincontext.